2013
DOI: 10.1002/14651858.cd005179.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for needle-related procedural pain and distress in children and adolescents

Abstract: The objectives are as follows: To assess the efficacy of cognitive-behavioral psychological interventions for needle-related procedural pain and distress in children and adolescents. Psychological interventions for needle-related procedural pain and distress in children and adolescents (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
163
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(173 citation statements)
references
References 183 publications
1
163
1
8
Order By: Relevance
“…Several reviews (Uman et al, 2006), Schechter et al (2007) reported that preparation is effective in reducing children's anxiety and pain of needles; however, these studies were conducted in a medical setting. For healthy children, although ''Teddy Bear Hospital'' reduces preschooler's anxiety toward hospitalization (Bloch & Toker, 2008) and increases knowledge about their body (Leonhardt et al, 2013), it doesn't focus on needles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews (Uman et al, 2006), Schechter et al (2007) reported that preparation is effective in reducing children's anxiety and pain of needles; however, these studies were conducted in a medical setting. For healthy children, although ''Teddy Bear Hospital'' reduces preschooler's anxiety toward hospitalization (Bloch & Toker, 2008) and increases knowledge about their body (Leonhardt et al, 2013), it doesn't focus on needles.…”
Section: Discussionmentioning
confidence: 99%
“…Needle-related procedures are a common source of pain and distress for children (Uman et al, 2006). Vaccination, which is the most common needle-related medical procedure, causes great anxiety for many children (Schechter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted under the following conditions to reduce as much as possible differences in the levels of pain and stimulation caused by injections [7,11,13]: 1) Injections were administered by one physician; 2) Only inactivated vaccines were used; 3) A single dose of 0.5 ml was administered to all patients; 4) The site of injection was the extensor surface of the upper arm; and 5) Only 27G short bevel needles were used. Children's previous experiences with injection also impact their pain and anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…This technique aims to draw children's attention away from medical procedures using moving toys or other things to alleviate their pain and distress as much as possible [12]. However, distraction studies that have set narrow parameters for certain variables, such as age, have not been significantly conducted [13]. Also, few previous studies have examined the effects of different kinds of distraction occurring simultaneously by focusing on children under five years of age receiving immunizations.…”
Section: Introductionmentioning
confidence: 99%
“…We feel that, in addition, research should focus on the best way to assess and treat the pain associated with the diseases that were subject of this survey. Next to pharmacological pain relief, the effectiveness of nonpharmacological interventions should be studied as well (30,31). The next challenge would be to disseminate information about successful pain management to those settings that treat children suffering from these diseases.…”
mentioning
confidence: 99%